Processing Technical Daily Reports in Offshore Petroleum Engineering - An Experience - Miura, Kazuo; Guilherme, Ivan Rizzo [UNESP]; Morooka, Celso Kazuyuki; Pelaquim Mendes, Jose Ricardo (Fuji Technology Press, 2003)
This paper reports ten years experience with the use of a methodology to extract and to consolidate expert knowledge from technical reports in Petroleum Engineering. The methodology here presented is based on the context of sensitive text analysis. The experience acquired from the present study is discussed and benefits obtained for the petroleum industry are highlighted*
Keywords: knowledge acquisition; petroleum industry; text categorization; text mining